Biomarker and hematological fieldwork with amphibians: is it necessary to sample all night? - Brodeur, Celine Marie; Bahl, María Florencia; Natale, Guillermo Sebastian; Poliserpi, Maria Belen (Springer, 2020)
In the context of the global amphibian crisis, biomonitoring constitutes a valuable assessment tool to provide critical up to date information on the status and health of amphibians worldwide. The aim of the current study was to evaluate the possible confounding effects of sex, size, and time since capture on enzymatic biomarkers and hematologic parameters of the South American frog Leptodactylus latrans. Frogs were collected by hand between 9 pm and 12 am on two consecutive nights. On the first night, captured frogs were transported for 2 h by car to laboratory installations, maintained overnight in plastic containers, and blood and tissue sampled on the next morning. In contrast, frogs collected on the second night were blood and tissue sampled in the field, immediately after the capture period. Hematological parameters were analyzed, and enzymatic activities of catalase, cholinesterase (ChE), and glutathione S-transferase (GST) were determined in the plasma, liver, kidney, and muscle. A sex difference was observed only for total white blood cell counts (WBC), females exhibiting significantly greater values than males. The packed cell volume (PCV), mean corpuscular hemoglobin concentration (MCHC), WBC, and muscle ChE activity were significantly correlated with snout-vent length (SVL). The correlation was inversed in the case of MCHC, WBC, and muscle ChE, while the correlation was positive between PCV and SVL. Most examined parameters presented similar values when frogs were sampled at night following capture or the next morning. Total red blood cells (RBCs) count, and plasma enzymatic activities of ChE and GST were the only parameters that presented significantly increased values in morning samplings compared with night samplings. Overall, the current study indicates that it is best to sample the frogs as soon as possible after capture if hematologic or plasmatic biomarkers are examined. Nevertheless, it is possible to sample on the next morning if tissular biomarkers are employed.